Increased Growth-Inhibitory and Cytotoxic Activity of Arsenic Trioxide in Head and Neck Carcinoma Cells with Functional p53 Deficiency and Resistance to EGFR Blockade - Boyko-Fabian, Mariya (Public Library of Science, 2014)
BACKGROUND AND PURPOSE: Mutations in the p53 gene are frequently observed in squamous cell carcinoma of the head and neck region (SCCHN) and have been associated with drug resistance. The potential of arsenic trioxide (ATO) for treatment of p53-deficient tumor cells and those with acquired resistance to cisplatin and cetuximab was determined. MATERIAL AND METHODS: In a panel of 10 SCCHN cell lines expressing either wildtype p53, mutated p53 or which lacked p53 by deletion the interference of p53 deficiency with the growth-inhibitory and radiosensitizing potential of ATO was determined. The causal relationship between p53 deficiency and ATO sensitivity was evaluated by reconstitution of wildtype p53 in p53-deficient SCCHN cells. Interference of ATO treatment with cell cycle, DNA repair and apoptosis and its efficacy in cells with acquired resistance to cisplatin and cetuximab was evaluated. RESULTS: Functional rather than structural defects in the p53 gene predisposed tumor cells to increased sensitivity to ATO. Reconstitution of wt p53 in p53-deficient SCCHN cells rendered them less sensitive to ATO treatment. Combination of ATO with irradiation inhibited clonogenic growth in an additive manner. The inhibitory effect of ATO in p53-deficient tumor cells was mainly associated with DNA damage, G2/M arrest, upregulation of TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) receptors and apoptosis. Increased activity of ATO was observed in cetuximab-resistant SCCHN cells whereas cisplatin resistance was associated with cross-resistance to ATO. CONCLUSIONS: Addition of ATO to treatment regimens for p53-deficient SCCHN and tumor recurrence after cetuximab-containing regimens might represent an attractive strategy in SCCHN.